The adolescent experience of hereditary angioedema: a qualitative study of disease burden and treatment experience - Lynne Broderick; April Foster; Laura Tesler Waldman; Laura Bordone; Aaron Yarlas (Orphanet Journal of Rare Diseases)
Abstract Background Hereditary angioedema (HAE) is a rare, autosomal dominant disorder causing swelling attacks in various parts of the body, resulting in impacts on health-related quality of life (HRQoL). The symptoms of HAE and its impacts on HRQoL have been well-documented in adults; however, relatively little is known about the experiences of adolescents with HAE. The objective of this study was to use qualitative interviews to investigate how adolescents experience HAE symptoms and how HAE impacts their HRQoL. Methods This was a non-interventional, qualitative study of adolescents with HAE. Participants were recruited via a patient advocacy organization and were eligible to take part in this study if they had a confirmed diagnosis of type I or type II HAE and were currently on prophylactic treatment to prevent HAE attacks. All participants completed a one-to-one, 60-minute, remote interview designed to elicit their experiences of HAE. Interview data were coded and analyzed using NVivo qualitative software. Results Twelve adolescents took part in this study. HAE attacks were described as painful and uncomfortable. Attacks varied by trigger, frequency, severity, location, and duration. Participants described ways in which HAE impacted their daily lives, including impacts on physical, social, emotional, and cognitive functioning, in addition to sleep disturbance, school-related impacts, and a need to avoid attack triggers. Impacts on emotional and social functioning were particularly noteworthy, as participants reported having to miss or skip social events, and sometimes withdrawing socially. Since initiating prophylaxis, participants reported the frequency, severity, and duration of attacks had been reduced and their HAE-related impacts had been minimized. Participants were satisfied with their current prophylactic and acute treatments, and expressed a preference for treatments that were effective, convenient, self-administered, and had minimal side effects. Conclusion Adolescents with HAE reported experiencing a range of symptoms that, when untreated, impacted their HRQoL in ways that are unique from adults. Further, participants reported that effective treatments (prophylactic and acute) inhibited symptoms and HRQoL impacts with minimal treatment burden. Findings from this study suggest that health care providers and clinical investigators should consider the unique HRQoL impacts experienced by adolescents when evaluating treatment benefit.